2008
DOI: 10.15666/aeer/0602_013019
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm ( Eisenia Fetida ) Bioassay to Assess the Possible Effects of Platinum Tailings Disposal Facilities on the Environment Along a Gradient

Abstract: Abstract. Platinum mines produce large amounts of inorganic tailings containing high levels of metals which are disposed of on tailings disposal facilities (TDFs) and there is no information available on their possible effects on the surrounding terrestrial environment. The aim of this study was to do an earthworm bioassay of soils along a gradient from a TDF over a period of 28 days in terms of growth, reproduction and metal accumulation. After 28 days the earthworms in the soil collected up to 1 km away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Onuoha and Worgu (2011) detected E. andrei mortality when applying Cd, Pb and Zn combinations (1000 mg kg À 1 soil) on OECD soils. Maboeta et al (2008), when evaluating a South African soil contaminated with 353 mg kg À 1 Zn and 32 mg kg À 1 Cu, verified weight loss in this earthworm species. Once the swine manure has substantial concentrations of these elements, this could be a possible explanation for the mortality observed in the presence of increasing concentrations of the swine manure in the Entisol, especially related to the presence of bioavailable forms of these metals in this soil after waste disposal.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Onuoha and Worgu (2011) detected E. andrei mortality when applying Cd, Pb and Zn combinations (1000 mg kg À 1 soil) on OECD soils. Maboeta et al (2008), when evaluating a South African soil contaminated with 353 mg kg À 1 Zn and 32 mg kg À 1 Cu, verified weight loss in this earthworm species. Once the swine manure has substantial concentrations of these elements, this could be a possible explanation for the mortality observed in the presence of increasing concentrations of the swine manure in the Entisol, especially related to the presence of bioavailable forms of these metals in this soil after waste disposal.…”
Section: Discussionmentioning
confidence: 73%
“…When the tropical natural soils contain less clay or OM and, consequently, there is a lower amount of negative charges followed by less adsorption of cations to the clay minerals (low CEC), therefore the metals become more available in the soil solution (Juo and Franzluebbers, 2003). In addition, several authors demonstrated that the availability of some metallic ions may cause adverse effects to the earthworms' development or reproduction, as reported for Cr(III) and Cr(IV) (Sivakumar et al, 2005, Cu (Spurgeon et al, 1994Maboeta et al, 2008) and Zn (Reinecke et al, 2001), which are also found at high concentrations in the swine manure (Gräber et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Worms were considered dead if they lacked any movement and did not respond to a definite tactile stimulus to the anterior end. Because earthworms tend to disintegrate quickly after death, absent worms were considered to have died (Maboeta et al, 2008). Cocoons were separated from each container by hand sorting.…”
Section: Methodsmentioning
confidence: 99%
“…Different effects between the evaluated soils occurred because one of them had lower clay content, which may result in lower adsorption of certain metal cations in the clay minerals, making them more available, thus affecting the reproduction of earthworms and enchytraeids. These effects have been demonstrated in studies such as Sivakumar and Subbhuraam 26 with Cr(III) and Cr(VI) 27 , and Maboeta 28 with Cu and Reinecke 29 with Zn. Gräber 30 claim that Cu and Zn mobility and availability, for instance, are influenced by soil characteristics, including clay content.…”
Section: Discussionmentioning
confidence: 70%